Evaluasi Penerapan E-government Di Pemerintah Kota Batu Menggunakan Kerangka Kerja Pemeringkatan E-government Indonesia (PeGI) - Ridho Fadhlurrahman; Mochammad Chandra Saputra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of e-government is one form of government efforts to create an open, clean and accountable bureaucracy by utilizing information technology. Commitment on e-government development is stated in Presidential Instruction No. 3 of 2003 on National Policy and Strategy of E-government Development. As part of government agencies in Indonesia, Batu City Government began implementing e-government to maximize the performance of its government. This study aims to assess the application of e-government in the Batu City Government by studying three Batu City Government division, which are Communications and Informatics Service, Regional Development Planning, Research and Development Agency and Agricultural Service. The Assessment was conducted by using the Indonesia e-Government Ranking Framework (PeGI) which focuses on policy dimensions and planning dimensions. The research methodology used is qualitative descriptive by using questionnaire for data collection, interview, and observation. Based on the results, it was found that the implementation of e-government in the policy dimension in Communications and Informatics Service is in the good category, Regional Development Planning, Research and Development Agency is in very less category and the Agricultural Service is in very less category. While in the planning dimension, the Communications and Informatics Service is in the less category, Regional Development Planning, Research and Development Agency is in the less category and the Agricultural Service is in the less category. From the results of the study then prepared recommendations for improvement of e-government services to achieve conditions of implementation with very good category based on the PeGI framework.